'… you kind of frantically go from one thing to the next and there isn't any time for thinking any more': a reflection on the impact of organisational change on relatedness in multidisciplinary teams. Issue 2 (3rd March 2016) - Nutt, Katherine; Keville, Saskia
Abstract: This paper reflects on the relational impact on Clinical Psychologists of NHS organisational change in the context of cuts and reorganisation. The reflections illustrate one theme drawn from a study of eight Clinical Psychologists working within adult Community Mental Health Multi-Disciplinary Teams. The paper considers the impact of competition and change in healthcare on the ability to engage in reflective practice potentially affecting client care due to reduced joint-working, consistency and creativity. The paper considers how acts of kindness (compassion) within organisational contexts at all levels can facilitate relatedness, reflection and more human care. It concludes by considering how shifting from short-term planning evaluating efficiencies based on perceived financial value, to thinking more widely and long-term about relational value may be of benefit to clinicians, clients and the system as a whole.